"Autistic people"? Who do you mean?. (2019) - Levy, Yonata
Abstract: Jaswal & Akhtar (J&A) offer evidence against lack of social motivation in "autistic people, " providing no further phenotypic details as to the autism spectrum disorder (ASD) subgroups that they refer to. I will argue that given the extensive behavioral and neurobiological heterogeneity among people who receive the diagnosis, reference to "autistic people" is misleading. As a consequence, J&A's claims are difficult to interpret.